Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1097/00006454-200305000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We conducted a prospective evaluation for evidence of the HIV-associated lipodystrophy syndrome of 26 children infected with HIV-1. Six children had evidence of body fat redistribution. Nine children showed laboratory evidence of insulin resistance. All children with body fat distribution or insulin resistance had been treated with protease inhibitors. Children treated with protease inhibitors had higher total cholesterol, higher low density lipoprotein-cholesterol and higher triglycerides than untreated child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…The prevalence of fat abnormality here was substantially higher than the 18-33% reported in other paediatric studies[8, 10-12, 31-33], reflecting variations in LS definitions and methodology, and underlying population differences. However, restricting the definition to moderate and severe cases resulted in a prevalence of 19%.…”
Section: Discussioncontrasting
confidence: 75%
“…The prevalence of fat abnormality here was substantially higher than the 18-33% reported in other paediatric studies[8, 10-12, 31-33], reflecting variations in LS definitions and methodology, and underlying population differences. However, restricting the definition to moderate and severe cases resulted in a prevalence of 19%.…”
Section: Discussioncontrasting
confidence: 75%
“…Insulin resistance is characterized by reduced insulin stimulation of glucose use by adipose tissue and muscles resulting in increased pancreatic insulin production, and is associated with obesity, dyslipidaemia, hypertension and type 2 diabetes in children [ 220 ]. Both PIs and NRTIs are associated with insulin resistance through inhibition of GLUT-4 transporters in myocytes and adipocytes, causing decreased uptake of glucose by these tissues [ 221 , 222 ]. HAART-associated body composition changes such as central obesity, resulting in fat deposition in muscle cells, may also contribute to insulin resistance [ 223 ], but data are inconclusive [ 224 , 225 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown differing results on the association of glucose homeostasis with PIs and LD syndrome [48,49]. Impaired glucose homeostasis has been reported among 8–35% of HIV-infected children [31]. However, no differences were detected in fasting serum insulin, proinsulin, C-peptide, insulin:glucose ratio or Homeostasis Model of Assessment (HOMA-IR) between PI-treated and PI-naïve children [48,5052].…”
Section: Lipodystrophy Syndromementioning
confidence: 99%